2021
DOI: 10.1186/s40035-021-00272-z
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on cytoskeletal dysregulation and mitochondrial mislocalization in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by selective, early degeneration of motor neurons in the brain and spinal cord. Motor neurons have long axonal projections, which rely on the integrity of neuronal cytoskeleton and mitochondria to regulate energy requirements for maintaining axonal stability, anterograde and retrograde transport, and signaling between neurons. The formation of protein aggregates which contain cytoskeletal proteins, and mitochondrial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 148 publications
1
27
0
Order By: Relevance
“…Impairments in axonal trafficking have been closely linked with various neurodegenerative disorders, including ALS [ 65 ]. Motor neuron axons of patients with ALS have been observed to accumulate large quantities of phosphorylated neurofilament proteins and organelles, resulting in swelling along the length of the axons [ 66 , 67 ]. Though the exact mechanisms behind axonal transport dysregulation are unknown, research has found both anterograde and retrograde transport hindered in the presence of mutant SOD1 protein in isogenic mouse models prior to the development of ALS-like symptoms [ 68 , 69 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Impairments in axonal trafficking have been closely linked with various neurodegenerative disorders, including ALS [ 65 ]. Motor neuron axons of patients with ALS have been observed to accumulate large quantities of phosphorylated neurofilament proteins and organelles, resulting in swelling along the length of the axons [ 66 , 67 ]. Though the exact mechanisms behind axonal transport dysregulation are unknown, research has found both anterograde and retrograde transport hindered in the presence of mutant SOD1 protein in isogenic mouse models prior to the development of ALS-like symptoms [ 68 , 69 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…This finding is in line with previous observations that NfH levels were associated with clinical progression in amyotrophic lateral sclerosis. 17 , 18 , 19 , 20 Cognitive impairment in PD is heterogeneous, and single or multiple cognitive domains can be affected in patients with PD who have cognitive impairment. 32 In the present study, cNfH levels were associated not only with decline in global cognition (MoCA), but also decline in domain-specific cognition, including visuospatial function (JLO), cognitive processing speed (SDM), verbal learning and memory (HVLT), executive function (SFT), and attention and working memory (LNS).…”
Section: Discussionmentioning
confidence: 99%
“… 16 Higher cNfH and blood NfH levels at baseline were associated with rapid progression of disease in patients with amyotrophic lateral sclerosis. 17 , 18 , 19 , 20 However, the association between the levels of NfH and clinical progression in patients with PD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although pathogenic genes have been screened, the mechanism of MN degeneration is still not completely clear. At present, it is considered related to a long list of factors, among which are disturbances in RNA metabolism [16], protein misfolding and aggregation [17], marked neuromuscular junction (NMJ) abnormalities [18], immune system deficiency [19], nucleocytoplasmic transport defects [20], impaired DNA repair [21], excitotoxicity [22], mitochondrial dysfunction [23], oxidative stress [24], cytoskeletal derangements [25], axonal transport disruption [26], neuroinflammation [27], oligodendrocyte dysfunction [28] and vesicular transport defects [29].…”
Section: Introductionmentioning
confidence: 99%